2005
DOI: 10.1177/003693300505000110
|View full text |Cite
|
Sign up to set email alerts
|

Can Alcohol Intoxication be Excluded as the Cause of Confusion following Head Injury?

Abstract: Confusion in the head injured patient with a BrAC of less than 1 mg/L, should alert one to the likelihood of causes other than alcohol intoxication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Patients observed at the OAEOC are hospitalised if they do not regain full consciousness within 4 h. The 4-h limit was set as patients poisoned by ethanol or heroin, the two most frequent toxic agents, should be awake and recovering by this time. If not awake or if confusion persists, other conditions must be suspected, most of them beyond the scope of what can be managed in the outpatient setting [ 15 , 16 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients observed at the OAEOC are hospitalised if they do not regain full consciousness within 4 h. The 4-h limit was set as patients poisoned by ethanol or heroin, the two most frequent toxic agents, should be awake and recovering by this time. If not awake or if confusion persists, other conditions must be suspected, most of them beyond the scope of what can be managed in the outpatient setting [ 15 , 16 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the research findings in this area are inconclusive. Although some researchers have concluded that GCS scores are lowered by alcohol intoxication and thus fail to provide an accurate evaluation of brain injury severity [6][7][8][9][10][11][12][13], a number of studies have found that blood alcohol levels (BALs) have no effect on GCS [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These effects are explained by CNS deterioration caused by the synergistic effects of brain damage and alcohol intoxication in the initial phase after brain injury [14]. Contrary to the general expectation of clinicians that alcohol intoxication in patients with brain injury would decrease consciousness, other studies have shown that BAC was not associated with GCS reduction in patients with TBI [12][13][14][15][16]. In a study of 1,075 patients with blunt TBI by Sperry et al [16], alcohol intoxication did not show a significant association with lower GCS scores in patients with TBI, and even high BACs (>250 mg/dL) did not affect the GCS score.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that GCS scores were decreased by alcohol [8][9][10][11]. However, other studies have also reported that the blood alcohol concentration (BAC) did not affect the GCS score [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%